Clumsy Solutions for a Complex World
XIII, 255 p.
Keywords: Clumsy Solutions for a Complex World is a powerful and original statement on why well-intended attempts to alleviate pressing social ills too often derail, and how effective, efficient and broadly acceptable solutions to social problems can be found.